The Devil they Knew: Chemical Documents Analysis of Industry Influence on PFAS Science - Nadia Gaber; Lisa Bero; Tracey J. Woodruff (Ubiquity Press, 2023)
Background: Per-and polyfluoroalkyl substances (PFAS) are a class of widely-used chemicals that persist in the environment and bioaccumulate in humans and animals, becoming an increasing cause for global concern. While PFAS have been commercially produced since the 1940s, their toxicity was not publicly established until the late 1990s. The objective of this paper is to evaluate industry documents on PFAS and compare them to the public health literature in order to understand this consequential delay. Methods: We reviewed a collection of previously secret industry documents archived at the UCSF Chemical Industry Documents Library, examining whether and how strategies of corporate manipulation of science were used by manufacturers of PFAS. Using well-established methods of document analysis, we developed deductive codes to assess industry influence on the conduct and publication of research. We also conducted a literature review using standard search strategies to establish when scientific information on the health effects of PFAS became public. Results: Our review of industry documents shows that companies knew PFAS was "highly toxic when inhaled and moderately toxic when ingested" by 1970, forty years before the public health community. Further, the industry used several strategies that have been shown common to tobacco, pharmaceutical and other industries to influence science and regulation - most notably, suppressing unfavorable research and distorting public discourse. We did not find evidence in this archive of funding favorable research or targeted dissemination of those results. Conclusions: The lack of transparency in industry-driven research on industrial chemicals has significant legal, political and public health consequences. Industry strategies to suppress scientific research findings or early warnings about the hazards of industrial chemicals can be analyzed and exposed, in order to guide prevention.